Do Outside Directors Tell the Truth, the Whole Truth and Nothing but the Truth when They Resign - BAR-HAVA, Keren (Institutional Knowledge at Singapore Management University, 2015)
This study examines the information content of the reasons for resignations by outside directors. Since directors are privy to private information about the firm, they may resign when they foresee future underperformance of the firm in order to reduce or eliminate damage to their reputation because of the poor future performance. However, in such cases directors have strong economic incentive not to disclose the true reason for the resignation in order to avoid loss of wealth through equity ownershipand impact on future directorships, and damage to business relationships. The results are consistent with this conjecture. Specifically, while resignations in general are associated with poor financial and operating performance, as well as with future litigations, there is no relation between the categories of resignations, formed on the basis of the reasons for departure, andfuture financial and operating performance. In addition, all categories are positively associated with future litigation. These results suggest that not all departing directors tell the truth, the whole truth, and nothing but the truth when they resign.